Out-of-Plane Behavior of Masonry Wall Strengthened Using Expanded Wire Mesh - Kanchidurai, S; A. Krishanan, P; Baskar, K; Saravana Raja Mohan, K (International Journal of Engineering and Technology, 2018)
Brick masonry is the principal part of the construction industry. This paper presents the result of the expanded wire mesh embedded into the masonry wall panel; expanded mesh (EM) is the inexpensive locally available material on the market. Through the experimental study, the primary affecting parameters recognized, and the methodology of the embedment details established, the preliminary survey was conducted as per the guidelines are given in the ASTM E518. Totally three numbers of control specimen and three numbers of EM embedded specimen are cast, and compressive strength test of masonry prism also evaluated to identify the crack propagation path. The test results turned out to be highly promising, out of plane damage was less in the EM embedded specimen also it was designated the cracks are reduced.